FGF receptor-4 (FGFR4) polymorphism acts as an activity switch of a membrane type 1 matrix metalloproteinase–FGFR4 complex - Sugiyama, Nami (National Academy of Sciences, 2010)
Tumor cells use membrane type 1 matrix metalloproteinase (MT1-MMP) for invasion and metastasis. However, the signaling mechanisms that underlie MT1-MMP regulation in cancer have remained unclear. Using a systematic gain-of-function kinome screen for MT1-MMP activity, we have here identified kinases that significantly enhance MT1-MMP activity in tumor cells. In particular, we discovered an MT1-MMP/FGF receptor-4 (FGFR4) membrane complex that either stimulates or suppresses MT1-MMP and FGFR4 activities, depending on a tumor progression-associated polymorphism in FGFR4. The FGFR4-R388 allele, linked to poor cancer prognosis, increased collagen invasion by decreasing lysosomal MT1-MMP degradation. FGFR4-R388 induced MT1-MMP phosphorylation and endosomal stabilization, and surprisingly, the increased MT1-MMP in return enhanced FGFR4-R388 autophosphorylation. A phosphorylation-defective MT1-MMP was stabilized on the cell surface, where it induced simultaneous FGFR4-R388 internalization and dissociation of cell–cell junctions. In contrast, the alternative FGFR4-G388 variant down-regulated MT1-MMP, and the overexpression of MT1-MMP and particularly its phosphorylation-defective mutant vice versa induced FGFR4-G388 degradation. These results provide a mechanistic basis for FGFR4-R388 function in cancer invasion.